Neuromuscular Electrical Stimulation as a Potential Countermeasure for Skeletal Muscle Atrophy and Weakness During Human Spaceflight - Maffiuletti, Nicola A.; Green, David A.; Vaz, Marco Aurelio; Dirks, Marlou L. (Frontiers in Physiology, 2019)
Human spaceflight is associated with a substantial loss of skeletal muscle mass and muscle strength. Neuromuscular electrical stimulation (NMES) evokes involuntary muscle contractions, which have the potential to preserve or restore skeletal muscle mass and neuromuscular function during and/or post spaceflight. This assumption is largely based on evidence from terrestrial disuse/immobilization studies without the use of large exercise equipment that may not be available in spaceflight beyond the International Space Station. In this mini-review we provide an overview of the rationale and evidence for NMES based on the terrestrial state-of-the-art knowledge, compare this to that used in orbit, and in ground-based analogs in order to provide practical recommendations for implementation of NMES in future space missions. Emphasis will be placed on knee extensor and plantar flexor muscles known to be particularly susceptible to deconditioning in space missions.